Mitigasi Emisi Gas Rumah Kaca Melalui Penerapan Irigasi Intermittent di Lahan Sawah Beririgasi - Widya Utaminingsih; Susi Hidayah (Jurnal Irigasi, 2012)
Mitigation of Green House Gases (GHGs) Emission through the implementation of intermittent irrigation on irrigated paddy field has been conducted. The aim of this study was to determine the mitigation potency by calculating the rate of growth of GHS’s emission and Global Warming Potential (GWP) on intermittent irrigation and conventional paddy field areas. GHGs’s (including CH4, CO2, and N2O) samples were collected in the irrigation area of Mrican Kanan Jombang on tertiary unit: TB 1 Ki, TB 2 Ki, TL4 Ka and conventional unit as data control. The samples were collected in three phases of rice growth which are: vegetative phase, primordia phase, and ripening fruit phase on boxes that catch GHGs. The samples were analyzed at the laboratory with chromatography gases (GC). Result from GHG’s flux indicated the values of GHG’s emission and GWP, thus the decline rate of GHG’s emission could be extracted. The study showed that the intermittent irrigation could reduce CH4 emission for about 33,18 percent and GHGs’ global warming potency for about 34,9 percent compared to conventional irrigation .